How to keep well in wartime - Great Britain. Ministry of Health ; Central Council for Health Education (Great Britain); Clegg, Hugh Anthony, 1900- (London : His Majesty's Stationery Office, 1943)
1943 1943 1940s 28 pages : illustrations GET YOUR SHARE OF AIR AND SUNSHINE from a stuffy room, especially from the dead atmosphere of a centrally heated one. It does not matter so much that the air should be fresh as that it should be on the move. Remember that you yourself are a furnace, continually stoked by food. In the combustion of food in your body — for example, by your muscles when you do physical work — heat is given off. You are a warm-blooded animal and your body is kept at a temperature above that of the air round you. Your normal temperature, as you may know, is 98.4° F., when taken under the tongue. (The temperature of your liver is in the region of 100° F.) An average comfortable indoor temperature, whether in shop, office, or living-room, is about 60° to 65° F. So, being hotter than the air round you, you will always be losing heat to it, just as hot water added to cold water will become less hot by losing heat to it. The cold water, of course, becomes warmer. Still Air Means Stuffy Rooms. If you could not lose the heat produced in your body you would die of heat-stroke; you would simply boil over. The chief way in which you lose heat is by the evaporation of water from your skin and lungs. When you get very hot you lose such a lot of water that it forms into visible drops on vour skin — as sweat. If the air is very moist then it will not be able to take up much moisture from your body. And if it is still as well it will not be able to carry away the heat you are giving out. With still, moist air round you, your temperature will tend to rise and you will feel hot, stuffy, and uncomfortable. So keep the air on the move. If the working process of mill or foundry demands a higher temperature than 65° you will need more than ever to get all the fresh air you can when not at work. In your living-rooms at home keep the air on the move and the temperature at a moderate level; overheated rooms are inadvisable from the point of view of both health and fuel economy. Sun-and-air Baths. If you are lucky you may spend your brief annual holiday in a burst of sunshine. But holiday or no, seize every opportunity you can of giving your skin a good airing. The air " bath " is just as important as the sun " bath." The sun bath can be taken in your garden just as well as at the seaside. This is worth remembering now that most of us have to take our holidays at home. The play of sun and air on the bare skin is stimulating and generally tones you up, especially if you have a sluggish circulation. The ultraviolet rays of the sun act on a fatty substance in your skin and turn it into Vitamin D, the anti-rickets vitamin. This makes it possible for children to have strong and well-formed bones. If it is very hot and you sit in the shade, the ultra-violet rays will still reach your skin from the clear blue sky. Precautions for Sun-bathers. You can have too much of a good thing, and you can have too much sun; you can in fact get sun- 5 420/BS/7/16/18